2023
DOI: 10.3390/vaccines11020298
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Geographical Distribution of COVID-19 across Nigeria (March 2020–July 2021)

Abstract: Globally, the novel corona virus infection has continued to witness a growing number of cases since December 2019 when the outbreak was discovered and noted in China. Despite this has not been well studied for the case of COVID-19, human contact, public moveableness and environmental variables could have an impact onairborne’spropagation and virus continuance, such as influenza virus. This study aimed to determine the seasonal variation and geographical distribution of COVID-19 across Nigeria. An internet base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
4
3
1
Order By: Relevance
“…Of note, the northern region with a lower COVID-19 pandemic prevalence35 compared with the southern region has the highest volume of EHS indicators utilisation as shown in this study. The highest volume recorded in the northern regions may be associated with the higher population in the regions relative to the southern regions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Of note, the northern region with a lower COVID-19 pandemic prevalence35 compared with the southern region has the highest volume of EHS indicators utilisation as shown in this study. The highest volume recorded in the northern regions may be associated with the higher population in the regions relative to the southern regions.…”
Section: Discussionsupporting
confidence: 51%
“…34 It is not surprising that any disruptions in routine health services would produce a higher and longer-lasting impact in most parts of Nigeria's northern regions. Of note, the northern region with a lower COVID-19 pandemic prevalence 35 compared with the southern region has the highest volume of EHS indicators utilisation as shown in this study. The highest volume recorded in the northern regions may be associated with the higher population in the regions relative to the southern regions.…”
Section: Evaluation Of Model Performancesupporting
confidence: 52%
“…The North-East had the least confirmed COVID-19 case in both 2020 and 2023. This contradicts findings byMoroh, et al (2023) where the lowest confirmed case was observed in the North-Central.The increase COVID-19 confirmed case from 2020 to 2023 and death case observed from 2020 to 2023 in South-West and North Central regions could be attributed to logistical, administrative, and social obstacles. These challenges ranged from shortage of testing and isolation centres, lack of medical equipment and personnel, non-involvement of social workers and low motivation of medical personnel.…”
contrasting
confidence: 89%
“…The South-West region of Nigeria consistently reported the highest confirmed cases of COVID-19 in both 2020 and 2023, aligning with the findings ofMoroh, et al (2023) research where the reason may be attributed to the fact that the first confirmed case of COVID-19 infection was observed in a state in South-West, Nigeria: thus, the area is susceptible to the transmission of the viral infection. Additionally, the government of Lagos State and the Federal government of Nigeria notably expanded testing facilities, contributing to an increased identification of cases.…”
supporting
confidence: 83%
“…This information is represented in Figure 5. (Badmus et al, 2023;Omede et al, 2023;Onwube et al, 2023;Adeyemi et al, 2023;Moroh et al, 2023;Taiwo et al, 2023) and elsewhere around the world (Triambak et al, 2023;Jameel et al, 2023;Mitra et al, 2023) focusing on understanding the behaviour of the disease through modelling, reproduction metrics, risk factors and other research approaches.…”
Section: Visualisation Of Covid-19 Datamentioning
confidence: 99%